ANALISIS KERUSAKAN KOMPONEN MOTOR STARTER UNIT EXCAVATOR 329 DL CATERPILLAR - Munawir, Munawir; Razi, Misru; Khalik, Abdul (ELEMEN : JURNAL TEKNIK MESIN, 2025)
Machines require an electrical system to function and operate. The electrical system consists of batteries. The battery provides electric current to other electrical components. Machines that can produce large twisting moments require a starter component, as previously known. Electric motors are usually equipped with a solenoid to drive the pinion gear to a ring gear mounted around a flywheel, or flywheel, mounted on the crankshaft. Results of visual inspections carried out on all parts of the Motor Stater excavator 329DL. There was no wear or damage found on the Caterpillar. After carrying out a visual inspection, take measurements of the parts. The starter motor, after carrying out measurements, shows results that are under the specifications based on SIS/GRPTS.